Kinematical analysis of Lubin's handspring followed forward stretched salto with double twist in horse vault - Zheng, Y.-X. (Journal of Anshan Normal University, 2004)
It is the superior movement that Lu Bin performed the handspring followed forwardstretched salto with double twist in horse vault. By analyzing the technical characteristics of his movement, we found its general kinematical law were found. Those theoretical and practical reference listswere provided for the Chinese gymnasts to develop and technique of this kind of movement.